A paradigm shift rhetoric and theory-practice gap in online higher education: A case study of an open university - Lee, Kyungmee (Proceedings of the International Conference on Networked Learning, 2016)
In this paper, I critically examine a theory-practice gap existing in online higher education (HE) with a particular focus on the significant discrepancies between social constructivist learning theories and actual instructional design (ID) practices in an open university context. I perceive theory not as universal or scientific truth but as a historical and discursive product (Foucault, 1970). In this perspective, the theory-practice gap is both the result and the evidence of the disjunction between the common understandings (or discourses) about online HE and the actual state (or realities) of it. This is, therefore, a much more complex social and educational phenomenon than simply a pedagogical issue of how to apply the legitimate learning theories to appropriate ID practices. To better grasp the complexity, I first describe the evolution of instructional technologies and theories of distance education (DE), a predecessor of online education. Second, I analyze one wide-spread academic discourse that has propagated online education as a new learning paradigm in HE and suggested social constructivist theories-informed instructional practices as a better way of doing online HE. This analysis is followed by a qualitative case study of the actual ID practices and circumstances in an open university in North America. By examining the gap between instructional theories and practices in this particular HE context, this study provides insights about how the gap has come into being and some valuable lessons for future research. At this moment, we are witnessing how the rhetoric of the learning paradigm shift in HE has become the doctrine we pursue to further produce the imperative of providing online education across all HE institutions including residential universities. Unless we challenge the social press of this rhetoric and deconstruct our current perspectives on online education, we can neither slow down this seemingly inexorable shift to online education nor fully grasp the actual state of online HE in which the theory-practice gap may continue to increase. Thus, this study ultimately aims to question our current taken-for-granted assumptions about legitimate online HE practices largely influenced by the rhetorical and come up with a more helpful lens to approach the theory-practice gap.